Numbers in Space: Differences between Concrete and Abstract Situations - Pecher, Diane; Boot, Inge (Frontiers in Psychology, 2011)
Numbers might be understood by grounding in spatial orientation, where small numbers are represented as low or to the left and large numbers are represented as high or to the right. We presented numbers in concrete (seven shoes in a shoe shop) or abstract (29 – 7) contexts and asked participants to make relative magnitude judgments. Following the judgment a target letter was presented at the top or bottom (Experiments 1-3) or left or right (Experiment 4) of the visual field. Participants were better at identifying letters at congruent than incongruent locations, but this effect was obtained only when numbers were presented in concrete contexts. We conclude that spatial grounding might have a smaller role for numbers in abstract than in concrete context.